Comparison on growth performance, body coloration changes and stress response of juvenile river catfish, Pangasius hypophthalmus reared in different tank background colour. (18th June 2019) - Mat Nawang, Siti Umey Syahirah; Ching, Fui Fui; Senoo, Shigeharu
Abstract: The effects of different tank background colours (green, black and white) on the growth performance and body coloration of juvenile river cafish, Pangasius hypophthalmus, were examined in this study. The experimental fish with an initial body weight (BW) 0.13 ± 0.05 g and total length (TL) 2.54 ± 0.37 cm were used, and groups of 15 fish per tank were randomly distributed. The experiment was conducted for 20 days as a triplicate for each treatment. Survival, growth in BW, body weight gain (BWG), total length (TL), total length gain (TLG), specific growth rate (SGR), condition factor, feed conversion ratio (FCR), swimming speed, body coloration and stress response were evaluated. River catfish reared in white and green tanks attained significantly higher BW, BWG, TL, TLG and SGR compared to the black tank. The white tank attained significantly better FCR compared to the black tank. River catfish showed the most active swimming behaviour in the green tank (5.49 ± 1.32 cm/s) while the least in the white tank (3.37 ± 0.93 cm/s). Body coloration of river catfish in the black tank showed almost pure black body coloration (75.59 ± 9.08), followed by the green tank (126.23 ± 17.46) and the white tank (148.19 ± 10.51). However, there was no significant difference in the stress level of river catfish reared in white and black tanks and insignificant to those reared in the green tank. The findings in this study showed that the white and green background colour tanks can be used for promoting growth of river catfish culture while the black background colour tank can enhance body coloration that is suitable as ornamental fish.